Use of renal risk drugs in a nation-wide Polish older adult population: an analysis of PolSenior database - Deskur-Śmielecka, Ewa (BMC Geriatr, 2019)
BACKGROUND: Numerous medications should be avoided, or require dose adjustment in subjects with impaired kidney function. We aimed to assess the prevalence of potentially inappropriate use of renal risk drugs in a nation-wide, community-dwelling Polish older adult population. METHODS: We analysed regular intake of 38 medications that should be avoided, requiring dose modification, increase the risk of pre-renal kidney injury, or may cause potassium retention in subjects with moderately to severely impaired renal function in the PolSenior data base (N = 4514, mean age 76 ± 11 yrs). Kidney function was assessed with short Modification of Diet in Renal Disease formula estimated glomerular filtration rate (sMDRD) and Cockcroft-Gault creatinine clearance (CC). RESULTS: There were 855 (19%) individuals with sMDRD < 60 ml/min/1.73m(2), and 1734 (38%) with CC <  60 ml/min. Among drugs that should be avoided, spironolactone (20.4% of patients as classified by sMDRD and 17.5% by CC), non-steroidal anti-inflammatory drugs (13.4 and 11.3%), hydrochlorothiazide (11.1 and 11.0%), and metformin (6.9 and 8.2%) were most frequently used. The most frequently used drugs requiring dose modification were piracetam (13.9% by sMDRD, and 11.9% by CC), digoxin (8.3 and 8.8%), and gliclazide (6.8 and 5.9%). Classification of a drug use as ‘appropriate’ or ‘inappropriate’ was discordant depending on the method of kidney function assessment (sMDRD or CC) in up to 30%. Subgroups with sMDRD < 60 ml/min/1.73m(2) and with CC <  60 ml/min were taking ≥2 drugs increasing the risk of pre-renal kidney injury more frequently than individuals with better kidney function (46.6 vs. 23.1 and 33.0% vs. 24.4%, respectively). There were 24.7% of individuals with sMDRD < 60 ml/min/1.73m(2) and 18.0% with CC <  60 ml/min taking 2 or more drugs increasing serum potassium level. The proportion of subjects with hyperkalaemia increased with the number of such drugs. CONCLUSIONS: Use of drugs that should be avoided or require dose adjustment due to renal impairment, and potentially inappropriate drug combinations is a common problem in older adults in Poland. Assessment of kidney function with sMDRD may result in overlooking of requirements for dose adjustment formulated based on creatinine clearance. TRIAL REGISTRATION: Not applicable.